2021
DOI: 10.1111/1346-8138.15977
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of programmed cell death 1 and programmed cell death ligand 1 in infiltrating inflammatory cells of lichen planus without administration of immune checkpoint inhibitors

Abstract: The concept of lichenoid tissue reactions (LTR) was proposed by Pinkus in 1973. 1 LTR refer to reactions in which epidermal keratinocytes are damaged by inflammatory cells infiltrating into the dermis, resulting in vacuolar or liquefaction degeneration of basal cells, and cell death/individual keratinization of keratinocytes. 1 LTR are classified into those with prominent (cell rich) and those with little (cell poor) cell infiltration. The prototype of the former reaction is lichen planus. 2 Programmed cell de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…In support of the present study, it has been shown that PD-1 and PD-L1 expression levels were minimal in 12 patients with LP compared to 12 patients with erythema multiforme in a study done by Shirouchi et al [ 25 ]. Moreover, Costa et al [ 4 ] reported reduced/absent expression of PD-L1 with lower levels of PD-1 + T-lymphocyte cells in the OLP patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In support of the present study, it has been shown that PD-1 and PD-L1 expression levels were minimal in 12 patients with LP compared to 12 patients with erythema multiforme in a study done by Shirouchi et al [ 25 ]. Moreover, Costa et al [ 4 ] reported reduced/absent expression of PD-L1 with lower levels of PD-1 + T-lymphocyte cells in the OLP patients.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the fact that PD-1/PD-L1 interaction inhibits lymphocyte activation, the study results support the hypothesis that decreased expression of PD-1 and PD-L1 in LP patients could accelerate lymphocyte infiltration and cause failure to regulate CD8 + T-lymphocytes targeting the epidermis in the pathogenesis of LP and also low PD-L1 expression may accelerate macrophage infiltration [ 25 ].…”
Section: Discussionsupporting
confidence: 71%
“…Finally, numerous papers [ 214 , 215 , 216 ] report that the PD-L1 protein overexpressed in the membrane of tumor cells can induce apoptosis in T lymphocytes, thus eliminating the antitumor response. This mechanism could operate early in OLP as well [ 217 , 218 , 219 , 220 , 221 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 Interestingly, expression of PD-1 and PD-L1, which is believed to lead to increased infiltration of lymphocytes and possibly macrophages in the epidermis, was found to be reduced in de novo lichen planus (LP) compared with erythema multiforme lesions, and potentially contributes to development of LP. 49 Psoriasis is characterized by increased keratinocyte proliferation, resulting in well-demarcated, scaly, erythematous plaques. 22 ICI-induced psoriasis accounts for approximately 4% of all cutaneous irAEs, 50 and development of guttate psoriasis or psoriasis involving > 10% of body surface area (BSA) has been found to be predictive of a good response to ICI therapy.…”
Section: Inflammatorymentioning
confidence: 99%
“…Cutaneous pathogens in the skin microbiome may lead to increased activation of the innate immune system, which in turn generates a Th1 response resulting in ICI‐associated lichenoid reactions 48 . Interestingly, expression of PD‐1 and PD‐L1, which is believed to lead to increased infiltration of lymphocytes and possibly macrophages in the epidermis, was found to be reduced in de novo lichen planus (LP) compared with erythema multiforme lesions, and potentially contributes to development of LP 49 …”
Section: Mechanisms Of Cutaneous Immune‐related Adverse Eventsmentioning
confidence: 99%